Synthesis and Evaluation of Anticancer Activity of Some Imidazothiazolyl, Imidazobenzothiazolyl and Dihydroimidazothiazolyl Coumarins - Srimanth, Kagne; Rao, Vedula Rajeswar; Krishna, Devarakonda R. (Arzneimittelforschung, 2002)
A series of 6-(2H-1-benzopyran-2-one-3-yl)imidazo[2,1-b]thiazoles (1), 2-(2H-1-benzopyran-2-one-3-yl)imidazo[2,1-b]benzothiazoles (2) and 3-(2H-1-benzopyran-2-one-3-yl)-5,6-dihydroimidazo[2,1-b]thiazoles (3) have been synthesized and evaluated for anticancer activity in vitro. The compounds showed very good activity against different tumor cell lines.
Keywords: 2H-Benzopyran-2-ones, anticancer activity in vitro, imidazobenzothiazoles, imidazothiazoles